Novel Use of a Self-Expandable Metal Stent with an Anti-Migration System for Palliative Drainage of a Pancreatic Cystic Neoplasm - Paramasivam, Rajesh Kumar; Ho, Shiaw-Hooi; Abdullah, Basri Jeet; Goh, Khean-Lee; Hilmi, Ida (JOP. Journal of the Pancreas, 2014)
Context There is scanty data on endoscopic palliative management of pancreatic cystic lesions that cause gastric outlet obstruction (GOO). This is the first case report that illustrates the use of a covered self-expandable metal stent (CSEMS) with an anti-migration system in the management of a symptomatic neoplastic cystic pancreatic lesion. Case report A 92-year-old Chinese female presented with partial GOO for 3 months. Examination revealed a non-tender epigastric mass with moderate abdominal distension. Esophagogastroduodenoscopy (EGD) showed a significant bulge at the posterior wall of the gastric antrum and food residue in the stomach. A CT scan of the abdomen showed a large pancreatic tail cystic lesion. Endoscopic ultrasound (EUS) showed a clear, non-septated cystic lesion measuring 9.7x10 cm arising from the pancreatic tail. Analysis of the aspirate revealed the following: Amylase: 3,200 units/L, CEA: 411 ng/mL, CA 19-9 812 U/mL and no malignancy. A Niti-STM Biliary Stent (NAGITM) was used for a cystogastrostomy. This procedure was complicated by a self-limiting intra-abdominal leak, stent migration and bleeding from a splenic artery pseudoaneurysm which was arrested with coil embolization. She progressed well after that with significant symptom improvement and no further complications. Conclusion This is the first case of a CSEMS with an anti-migration system that was used for decompression of a pancreatic cystic neoplasm (PCN). Novel use of this stent is a viable option as palliative management of a PCN in those not fit for surgery but caution needs to be exercised as there can be significant complications. Image: CT abdomen showing stent in-situ.